Giant M1 resonance on the ground and excited states in 2s1d-shell nuclei - Kachan, A.S.; Vodin, A.N.; Deiev, O.S.; Korda, L.P.; Korda, V.Yu.; Kurhuz, I.V.; Olejnik, S.M.; Timchenko, I.S. (Вопросы атомной науки и техники, 2020)
The gamma decay of the resonance-like structures observed in the reaction of radiative capture of protons by the nuclei ²²Ne, ²⁶Mg, ³⁰Si, ³⁴,³⁶S, and ³⁸Ar in the region of excitation energies of 7…12 MeV was studied. The excitation functions of this reaction were measured. The resonance strengths in the energy range of the accelerated protons Ep = 1.0…3.0 MeV were determined. The obtained discrete distributions of the magnetic dipole γ-transitions on the ground and excited states for the nuclei of the 2s1d-shell have resonance character. Giant M1 resonance on the ground and excited states in the ²³Na, ²⁷Al, ³¹P, ³⁵,³⁷Cl, and ³⁹K nuclei has been identified. The position of the M1 resonance on excited states coincides with that predicted by the Brink-Axel hypothesis for nuclei that are at the beginning of the subshell. Досліджено гамма-розпад резонансоподібних структур, які спостерігаються в реакції радіаційного захоплення протонів ядрами ²²Ne, ²⁶Mg, ³⁰Si, ³⁴,³⁶S і ³⁸Ar в області енергій збудження 7…12 МеВ. Виміряно функції збудження цих реакцій та визначено сили резонансів в області енергій прискорених протонів Ep = 1,0…3,0 МеВ. Отримані дискретні розподіли магнітних дипольних gamma;-переходів на основні та збуджені стани ядер 2s1d-оболонки мають резонансний характер. Ідентифіковано гігантський М1-резонанс на основних і збуджених станах в ядрах ²³Na, ²⁷Al, ³¹P, ³⁵,³⁷Cl i ³⁹K. Положення М1-резонансу на збуджених станах для ядер, що знаходяться на початку підоболонки, збігається з її значенням, передбаченим гіпотезою Брінка-Акселя. Исследован гамма-распад резонансоподобных структур, наблюдаемых в реакции радиационного захвата протонов ядрами ²²Ne, ²⁶Mg, ³⁰Si, ³⁴,³⁶S и ³⁸Ar в области энергий возбуждения 7…12 МэВ. Измерены функции возбуждения этих реакций и определены силы резонансов в области энергий ускоренных протонов Ep = 1,0…3,0 МэВ. Полученные дискретные распределения магнитных дипольных γ-переходов на основные и возбужденные состояния ядер 2s1d-оболочки имеют резонансный характер. Идентифицирован гигантский М1-резонанс на основных и возбужденных состояниях в ядрах ²³Na, ²⁷Al, ³¹P, ³⁵,³⁷Cl и ³⁹K. Положение М1-резонанса на возбужденных состояниях для ядер, находящихся в начале подоболочки, совпадает с ее значением, предсказанным гипотезой Бринка-Акселя.